การพัฒนาทักษะการเขียนสะกดคำโดยใช้แบบฝึกสาระการเรียนรู้ภาษาไทยนักเรียนชั้นประถมศึกษาปีที่ 3 โรงเรียนบ้านกะเตียด ตำบลสองคอน อำเภอโพธิ์ไทร จังหวัดอุบลราชธานี - หินอ่อน, สนอง; แสนสิ่ง, พีรพงษ์; พิจารณ์, วีรพงษ์ (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 1 No 2 (2024): วารสาร มมร ยศสุนทรปริทรรศน์ ปีที่ 1 ฉบับที่ 2 : พฤษภาคม - สิงหาคม 2567, 2024)
This research study is part of classroom research aimed at improving teaching and learning skills in education. The research objectives are to develop and compare the spelling achievement of third-grade students at Ban katiat School by using Thai language exercises focused on spelling. A quasi-experimental quantitative research method was employed, with a target group of 25 students. The study compared pre-test and post-test results using an 80/80 efficiency criterion. The research findings revealed that the development of the Thai language learning exercises achieved an efficiency score of 81.30/82.04, meeting the set criterion of 80/80. The comparison of learning outcomes showed that the post-test scores were significantly higher than the pre-test scores at the .05 level.